Pelaksanaan Audit Medis Rujukan Non Spesialistik (RNS) dengan Time, Age, Comorbid, Complication (TACC) pada Fasilitas Kesehatan Tingkat Pertama (FKTP) di wilayah Kota Administrasi Jakarta Utara - Indrianti Wakhyuni; Putri Wulandari; Darmawan Purnama; Elisa Adam (BPJS Kesehatan, 2021)
In the era of the National Health Security (Jaminan Kesehatan Nasional-JKN) program, the Primary Care Health Facility (Fasilitas Kesehatan Tingkat Pertama-FKTP) has become a frontline to management of non specialistic diagnoses, although it is still possible for non specialistic diagnoses to be referred to hospitals on the grounds of Time, Age, Complication, and Comorbidity (TACC) at National Health Insurance (Badan Penyelenggara Jaminan Sosial- BPJS Kesehatan) application system, but it is not yet known whether TACC is only used as for passing referrals, even though the actual condition of the patient can still be handled completely at the first level, or FKTP is actually not able to handle the diagnosis. Purposes: Data collection for this study was carried out through medical audit activities aimed at detecting whether TACC has been used according to the actual patient's condition or only as a means for passing referrals. Methods: Medical audit has compare the suitability between the choice of TACC in the BPJS Health application system and the patient's medical record. Results: The results of the medical audit, it was found that 32,8% of participants had discrepancy between the diagnosis writing and the TACC choice in the BPJS Health application system and medical records; medical records of 35,75% of participants have not been written in full in accordance with Regulation of the Minister of Health No. 269/2008 concerning Medical Records; and 44,62% of participants still received medical treatment that did not refer to the prevailing medical consensus. Keywords: TACC; Aplication System; Medical Record